Women's Life Writing and Early Modern Ireland - McAreavey, Naomi; Eckerle, Julie A., 1971- (Book collections on Project MUSE., 2019)
"Women's Life Writing and Early Modern Ireland focuses on women writing in and about seventeenth-century Ireland"--